2008
DOI: 10.1002/pmic.200700054
|View full text |Cite
|
Sign up to set email alerts
|

Unique proteomic features induced by a potential antiglioma agent, Nordy (dl‐nordihydroguaiaretic acid), in glioma cells

Abstract: Nordy is a chirally synthesized compound of a natural lipoxygenase inhibitor nordihydroguaiaretic acid. In this study, we found that Nordy inhibited the growth of human glioma cell lines in vitro and their tumorigenicity in mice. In addition, Nordy promoted differentiation of highly malignant human glioma cells. Investigation into the mechanistic basis of Nordy activities revealed that it altered the pattern of protein expression profiles in tumor cells. By using 2-DE, we found that in human glioma cell lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
14
1
Order By: Relevance
“…In our previous studies, we found Nordy treatment repressed growth of glioma cells in vitro and in vivo [6,7], but the present findings suggest growth inhibition of GSLCs could be occurring. We then asked whether Nordy treatment might target glioma cells as a whole or target GSLCs preferentially.…”
Section: Alox-5 Is Preferentially Expressed By Gslcs and Is Inhibitedcontrasting
confidence: 78%
See 3 more Smart Citations
“…In our previous studies, we found Nordy treatment repressed growth of glioma cells in vitro and in vivo [6,7], but the present findings suggest growth inhibition of GSLCs could be occurring. We then asked whether Nordy treatment might target glioma cells as a whole or target GSLCs preferentially.…”
Section: Alox-5 Is Preferentially Expressed By Gslcs and Is Inhibitedcontrasting
confidence: 78%
“…In our previous study, we revealed inhibition of glioma growth by Nordy treatment [7], but the mechanistic basis of such anti-glioma activity is largely unknown. In light of enhanced expression of Alox-5 in GSLCs, we tested whether Nordy, the racemate of a lipoxygenase inhibitor NDGA, could inhibit the enzymatic activity of Alox-5 in an in vitro assay system.…”
Section: Alox-5 Is Preferentially Expressed By Gslcs and Is Inhibitedmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, EIF5A plays an important role in hepatocellular carcinoma (HCC) tumorigenesis, and targeting EIF5A may offer new therapeutic alternatives to hepatocellular carcinoma patients [28]. In glioma, EIF5A was downregulated after Nordy treatment [29].…”
Section: Discussionmentioning
confidence: 99%